Development of anterior inferior cerebellar artery pseudoaneurysm after gamma knife surgery for vestibular schwannoma. A case report and review of the literature. (August 2014) - Sunderland, Geraint; Hassan, Faizul; Bhatnagar, Priya; Mitchell, Patrick; Jayakrishnan, Vijayam; Forster, David; Mendelow, Alexander David
Abstract Gamma knife surgery (GKS) is a well-established modality for controlling the progression of vestibular schwannomas. Adverse effects of this treatment are extremely rare but include cyst formation and malignant transformation. We report a case of anterior inferior cerebellar artery (AICA) pseudoaneurysm development rupture presenting as a poor WFNS grade subarachnoid haemorrhage. This is only the fourth case of aneurysm development (AICA aneurysm) following GKS reported but due to its serious nature we believe this potential complication warrants awareness in those offering this treatment.